2017
DOI: 10.1001/jamaneurol.2017.1014
|View full text |Cite
|
Sign up to set email alerts
|

Intensive Blood Pressure Reduction and Spot Sign in Intracerebral Hemorrhage

Abstract: IMPORTANCE The computed tomographic angiography (CTA) spot sign is associated with intracerebral hemorrhage (ICH) expansion and may mark those patients most likely to benefit from intensive blood pressure (BP) reduction.OBJECTIVE To investigate whether the spot sign is associated with ICH expansion across a wide range of centers and whether intensive BP reduction decreases hematoma expansion and improves outcome in patients with ICH and a spot sign. DESIGN, SETTING, AND PARTICIPANTS SCORE-IT (Spot Sign Score … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
63
0
3

Year Published

2017
2017
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 93 publications
(69 citation statements)
references
References 30 publications
3
63
0
3
Order By: Relevance
“…Intensive control of blood pressure may suppress the incidence of PRH, although its effect did not inhibit spontaneous expansion of sICH in patients with the spot sign in a secondary analysis of the Antihypertensive Treatment of Acute Cerebral Hemorrhage II (ATACH-II) trial. 18 This study has several limitations. The first is its retrospective, single-center design.…”
Section: Discussionmentioning
confidence: 92%
“…Intensive control of blood pressure may suppress the incidence of PRH, although its effect did not inhibit spontaneous expansion of sICH in patients with the spot sign in a secondary analysis of the Antihypertensive Treatment of Acute Cerebral Hemorrhage II (ATACH-II) trial. 18 This study has several limitations. The first is its retrospective, single-center design.…”
Section: Discussionmentioning
confidence: 92%
“…Since CTA spot sign stratifies the risk for ICH growth, it may serve as an imaging marker for anti-expansion treatments. Recently, Morotti et al [25] investigated whether CTA spot sign-positive patients are more likely to benefit from intensive BP reduction. However, the authors reported that intensive BP treatment was not associated with significant reduction of ICH expansion or improved functional outcome in spot sign-positive patients [25].…”
Section: Discussionmentioning
confidence: 99%
“…Im nativen Blutungs-CT oder mithilfe des Spot signs lassen sich keine Marker definieren, die den Nutzen einer RR-Senkung vorherzusagen erlauben [46,47].…”
Section: Intracerebrale Blutung Und Blutdrucksenkung: Studienlageunclassified